(untitled) (Journal of EAHIL, 2024)
Knowledge and library professionals in the UK are exploring the use of generative artificial intelligence (AI and contributing to discussions concerning data and knowledge, in the context of a country keen to drive the adoption of data driven services and digital technologies. In this article we introduce the drivers adoption of AI within NHS Knowledge and Library Services (KLS) in England, and the methodologies employed to upskill staff in new technologies. This is set against the backdrop of the ethics and risks associated with which provide opportunities for KLS to improve services and support the safe and effective adoption of AI follow up article we provide practical use case studies, to help inspire experimentation and adoption.